Phytochemical prospecting and antimicrobial evaluation of Sida planicaulis Cav. (Malvaceae) on pathogenic yeast - Sobreira, Ana Laura de Cabral; Oliveira, Nayana da Rocha; Costa, Danielly Albuquerque da; Carmo, Egberto Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Plant species are increasingly used as medicinal sources for the discovery of biologically active molecules. The species Sida planicaulis Cav. presents a distribution throughout the Brazilian territory, it is popularly known as “vassoura” and it is used in folk medicine to treat pain in the body. Although it is used by the community, this species does not have scientifically proven chemical or pharmacological studies. In this way, this work aimed to determine the chemical composition of BSE and the hexane, chloroform, ethyl acetate and hydroalcoholic phases of Sida planicaulis Cav. and evaluate the fungal potential against potentially pathogenic yeasts, using the values of inhibition halos to determine antifungal activity. The presence of alkaloids, flavonoids, steroids, triterpenes, saponins and tannins was observed in phytochemical prospecting. Yeast Candida tropicalis, Geotrichum 57839, Rhodotorula spp and Trichosporon inkin LM-67 presented resistance against BSE and the respective phases of Sida planicaulis Cav., with no halo of inhibition being observed. The study contributes to the extraction, purification and isolation of future secondary metabolites and suggests that BSE and the stages of Sida planicaulis Cav. are not used to treat infections caused by these fungi.